Fe-doped reconstruction of pyrite into defective Fe1-xS polymorphs for selective Cu-As separation from waste acid - Xingfei Zhang; Hongzhen Lei; Xianzhong Bu; Haisheng Han; Wei Sun; Chenglong Lu; Zihao Sun; Xuewen Song; Sen Wang; Jiwei Xue (Minerals Engineering, 2026)

A comparative study on radio frequency inactivation kinetics of Bacillus cereus vegetative cells and A. flavus spores in sunflower seeds: nonlinear modeling and its impact on storage stability - Xuan Ou; Sen Zeng; Jiamin Song; Songlei Wang; Yunyang Wang; Baozhong Cui; Guangxian Wang; Ping Zhang; Qiuyu Deng; Yinghua Tang; Yanan Sun (Food Research International, 2026)

Differentiation of block-scale carbon budgets and synergistic carbon reduction pathways under functional guidance and spatial constraints: Evidence from Wuxi, China - Hui Guo; Wei Sun; Sen Wang; Man Li (Sustainable Cities and Society, 2026)

SNAC4/9 negatively regulate the resistance of tomatoes to B. cinerea by suppressing phenylpropanoid metabolic pathway - Linxiang Qiao; Yijie Sun; Sen Cao; Xiaoyang Zhao; Xiaohui Qi; Jinting Lu; Caie Wu; Zhaohui Xue; Xiaohong Kou (Plant Science, 2026)

Effect of net submergence depth on the dynamic response of a bottom-supported aquaculture cage - Guo-Hai Dong; Qi-Ying Sun; Sen-Qi Cui; Chun-Wei Bi (Ocean Engineering, 2026)

Analytical modeling of water wave diffraction by arrays of non-concentric porous dual cylinders - Zhenfeng Zhai; Jiaqi Wang; Sen Wang; Chang Sun; Ying Li; Tiancong Zhao (Ocean Engineering, 2026)

Synergistic modification of wheat bran by fungal-enzymes: From wheat bran composition and properties modulation, gluten protein structure evolution, to wheat dough and noodle quality improvement - Mengyuan Li; Yanhua Li; Li Li; Xueling Zheng; Binghua Sun; Sen Ma (Food Chemistry, 2026)

Serum-free media for cultivated meat: from cellular mechanisms to cost-effective bioprocess design - Yongliang Liu; Yuhao Sun; Xiaojin Song; Ruihao Zhang; Tengsheng Qiao; Sen Wang; Kehou Pan; Haohao Wu; Hongwei Zheng; Changhu Xue (Critical Reviews in Food Science and Nutrition, 2026)

Antifungal effects of β-cyclodextrin/Carvacrol polyvinyl alcohol film against Aspergillus chevalieri in stored wheat grains - Chen Yang; Yi-Ming Wang; Wen-Bo Sun; Yang-Yong Lv; Huan-Chen Zhai; Shan Wei; Ping-An Ma; Yuan-Sen Hu; Shuai-Bing Zhang (Journal of Stored Products Research, 2026)

Study on defluorination performance and mechanism of Fe-Al modified oyster shell substrate coupled with microbially induced calcium precipitation for enhanced ecological floating beds - Sen Wang; Xueqi Wang; Yile Dai; Long Yang; Jingxin Song; Junqi Sun; Chunyan Zhai; Fanlong Kong; Shuo Li; Jiaxin Shi (Journal of Hazardous Materials, 2026)

Combined suppression of Aspergillus parasiticus and aflatoxin B1 in marinades: unraveling the cooperative antifungal mechanism of linalool and surfactin - Qiqi Sun; Zhanrui Huang; Wanying He; Lianhua Hu; Yuebo Li; Xiaohu Zhou; Hao Chen; Sen Tao (Food Research International, 2026)

Synergistic effects of molecular weight and dosage of wheat bran arabinoxylan on freeze-thawed dough quality: Governing water-ice dynamics - Mengyuan Li; Li Li; Binghua Sun; Xiaojie Qian; Jing Han; Sen Ma (Food Research International, 2026)

Hypoglycemic peptides from Xanthoceras sorbifolium Bunge seed meal: Preparation, identification, and mechanism via PI3K/Akt/GSK-3β signaling - Xiaoxue Zang; Sen Zhou; Xuan Guo; Guang Yang; Keqing Shi; Liangsheng Wang; Ziyan Zhang; Jie Sun (Food Bioscience, 2026)

Structural enhancement of zein-HPMC composite network for gluten-free buckwheat dough and biscuits quality: Assessing rheology, water dynamics, and microstructure - Zhenzhen Wang; Yang Wu; Yubin Wei; Sen Ma; Xiaojie Qian; Binghua Sun; Jing Han; Li Li (Food Hydrocolloids, 2026)

Delta-Band Dynamics of CaMKI-Positive Preoptic Neurons Encode Thermal Homeostatic Information - Dian-Dian Wang; Run-Zhou Yang; Song-Tang Sun; Ya-Lun Sun; Rui-Yu Wang; Xiao-Yan Meng; Sen-Miao Li; Jia-Kang Li; Pei-Pei Liu; Shu-Ang Li; Jian-Sheng Kang (Neuroscience Bulletin, 2026)

Impact of oxidative aging on asphaltene interfacial behavior and emulsion stability: Implications for water remediation - Qi Zhou; Yongxiang Sun; Sen Yang; Xuguang Song; Xiangyu Xiong; Hongbo Zeng (Water Research, 2026)

ASFV early protein p30 suppresses antiviral type I IFN induction by targeting TRIM21 and RIG-I like receptor signaling adaptor MAVS - Jiajia Zhang; Hanrong Lv; Jin Ding; Ziyan Sun; Chenglin Chi; Sizhuang Liu; Sen Jiang; Nanhua Chen; Wanglong Zheng; Jianzhong Zhu (Veterinary Microbiology, 2026)

Deep Learning-Enhanced Adaptive Correntropy Factor Graph Optimization for robust UUV navigation - Sen Cheng; Yanyan Wang; Bin Sun; Haitao Zhu; Xianqiang Qu (Ocean Engineering, 2026)

Sedimentation rate changes revealing the evolution of circum–Arctic ice sheets since the Last Interglacial - Song Zhao; Dong Wu; Yu-Ying Zhang; Chao Cui; Sen Shan; Peng Ren; Lin-Sen Dong; Wei-Bin Zhang; Shu-Wei Sun; Yan-Guang Liu (Global and Planetary Change, 2026)

Unveiling the impact of mixed-strain solid-state fermentation on wheat bran dietary fiber: gluten protein structure evolution, dough rheological modulation and steamed bread quality enhancement - Xinhao Li; Rui Huang; Mengyuan Li; Lingfang Zhang; Xiaojie Qian; Binghua Sun; Sen Ma; Li Li (Food Hydrocolloids, 2026)

Pre-homogenization heat treatment as a novel strategy to enhance oat milk stability: Unraveling the role of protein modification - Xiaojie Qian; Yang Wu; Binghua Sun; Cong Sun; Sen Ma; Xiaoxi Wang (Innovative Food Science & Emerging Technologies, 2026)

Influence of sand particle size on fire suppression performance of oil well fires in desert - Zhen Lou; Guangchao Sun; Kai Wang; Xinyu Chang; Hengjie Qin; Sen Li; Nian Jiang; Haowei Yao (Process Safety and Environmental Protection, 2026)

Association between lipid oxidation, water activity and aflatoxin B1 risk reversal in stored sunflower seeds: A storage microenvironment observation study - Sen Zeng; Jiamin Song; Xuan Ou; Tinyan Sang; Siying Lin; Ruixia Zhang; Jie Chen; Yuhua Tang; Songlei Wang; Yanan Sun (Journal of Stored Products Research, 2026)

Two melanin-deficient mutants of Harmonia axyridis exhibit distinct elytral carotenoid profiles compared to the wild type yet display similar stage-specific alterations - Yuan Li; Yuan-Xing Sun; Sen-Shan Wang; Ya-Nan Hao; Ting-Wei Zhang (Journal of Insect Physiology, 2026)

Integrated transcriptomic and metabolomic analyses reveal the mechanism of hypoxia tolerance in Aspergillus chevalieri under controlled nitrogen atmosphere - Yu-Liang Qin; Jing Ren; Wen-Bo Sun; Ying-Ying Wang; Shuai-Bing Zhang; Yang-Yong Lv; Huan-Chen Zhai; Yuan-Sen Hu (International Journal of Food Microbiology, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Laver cultivation mitigates zooplankton miniaturization in eutrophic coastal ecosystems - Sen Li; Jieqing Yang; Jinchen Yu; Tao Sun; Shuo Chen; Jin Zhou; Peng Zhang; Hong Huang (Hydrobiologia, 2026)

Evaluation of different types of isotope-labelled steroids based on liquid chromatography–mass spectrometry - Yameng Zhao; Luqi Sun; Pengshuai Zhang; Sen Xu; Shenghao Zhu; Lantao Zhang; Mingyang Hu; Jinglan Yu; Zhaocong Shang; Lin Zou; Wen Lei (Isotopes in Environmental and Health Studies, 2026)

Anti-leukemia steroidal saponins from Paris polyphylla var. yunnanensis - Yu Zhang; Yu-Chen Zhang; Yu-Chen Fan; Chen-Sen Xu; Hao-Lin Yu; Chao Wang; Jing Zhang; Yi-Lin Liu; Yi-Bo Shen; Chao Liu; Jin-Yue Sun; Jin-Zhong Hu; et al. (Phytochemistry, 2026)

A coupled B-C-H-W model for predicting wave-induced residual liquefaction of bio-grouted seabed around buried tunnels - Yujie Li; Changrui Dong; Sen Mei; Beifeng Lv; Xingye Sun; Peng Zhu (Ocean Engineering, 2026)

Molecular mechanisms of antifreeze activity in wheat bran arabinoxylan: The role of fine structure in modulating water-ice dynamic changes - Mengyuan Li; Binghua Sun; Li Li; Sen Ma (Food Research International, 2026)

Ultrasound-assisted deep eutectic solvent extraction of flavonoids from Chinese bayberry leaves: Optimization, molecular mechanism, and antioxidant evaluation - Ji-min Lv; Wang-ting Zhou; Chong-de Sun; Yan Cao; Qi-le Xia; Zeng-qun Zhou; Sen-miao Liang; Meng-ting Wang; Xing-jiang Qi (Food Chemistry, 2026)

Mechanisms of oat dough adhesion modulated by moisture-controlled roasting: The role of aqueous extracts - Binghua Sun; Ruige Yu; Xiaojie Qian; Fan Yang; Sen Ma; Chong Liu; Xiaoxi Wang (Food Hydrocolloids, 2026)

Wetland restoration for waterbird conservation: A framework and its application at Chongming Dongtan in China - Ningning Liu; Yanlin Cui; Sen Yang; Yihao Fang; Yue Ren; Shoudong Zhang; Huan Xu; Xuesong Feng; Wei Wu; Xuena Sun; Dongliang Niu; Ming Nie; et al. (Biological Conservation, 2026)

Characterization of a reassortant H3N2 swine influenza virus with 2009 pandemic internal genes and enhanced potential for zoonotic risk - Jun Jiao; Jin Ding; Ziyan Sun; Chenglin Chi; Sizhuang Liu; Sen Jiang; Nanhua Chen; Wanglong Zheng; Xiaoyan Ding; Jianzhong Zhu (Veterinary Microbiology, 2026)

A hybrid spatial framework for risk mapping and driving factor diagnosis of soil combined contamination in Guangzhou - Lian Chen; Zhenjiang Wang; Lingyun Sun; Zhipeng Wu; Sen Lin; Dan Wang; Jianan Wu; Zhiyi Li; Gaocong Li (Journal of Geochemical Exploration, 2026)

Changes in production and fate of anthropogenic nitrogen driven by environmental policies in China - Yang Xu; Jiatao Chen; Sen Du; Yuming Sun; Wencheng Ding; Yandong Xue; Li Gao; Yong Chen; Xuan Zhou; Jiangpeng Hu; Zhiping Duan; Zengyuan Li; et al. (Journal of Environmental Management, 2026)

Ionic liquid-modified hollow microspheres of tartaric acid-anion intercalated LDH in PIM-1 membranes for superior CO2/N2 separation - Caifeng Xia; Siyuan Liu; Qikang Yin; Sen Liu; Bo Liao; Shuxian Wei; Zhaojie Wang; Zhe Sun; Xiaoqing Lu (Journal of Environmental Chemical Engineering, 2026)

The interactive effects of roasting degree and lipid content on the gas retention capacity in fermented oat dough - Fan Yang; Wenhua Ma; Ruige Yu; Binghua Sun; Xiaojie Qian; Cong Sun; Chong Liu; Sen Ma; Xiaoxi Wang (Food Research International, 2026)

Biotic interactions driving the Centropages species co-existence in temporal Xiangshan Bay, China - Jieqing Yang; Yunrong Shi; Jinchen Yu; Lang Chen; Yuekai Wang; Tao Sun; Sen Li; Xinran Li; Qinghe Liu; Jing Fu; Wei Tian; Jin Zhou (Journal of Oceanology and Limnology, 2026)

Discovery of antimicrobial citrinin dimers from the mangrove-derived fungus Penicillium citrinum - Baodan Zhang; Longhui Liu; Sen Wang; Xiaoqi Sun; Guangrong Zi; Kui Hong; Liyan Sun; Ling Liu (Phytochemistry, 2026)

Corrigendum to “Non-monotonic effect of starch content on protein digestion in wheat noodles mediated by protein network structural changes” [Food Res. Int. 228 (2026) 118418] - Lingfang Zhang; Shuzhen Yang; Xiaojie Qian; Mengyuan Li; Sen Ma; Binghua Sun; Xiaoxi Wang (Food Research International, 2026)

Non-monotonic effect of starch content on protein digestion in wheat noodles mediated by protein network structural changes - Lingfang Zhang; Shuzhen Yang; Xiaojie Qian; Mengyuan Li; Sen Ma; Binghua Sun; Xiaoxi Wang (Food Research International, 2026)

Effect of Saturation State on Mudstone Mechanical Properties and the Fracture Zone Formation Around Mudstone Roadways - Jinghua Li; Guichen Li; Yuantian Sun; Fengzhen He; Haoran Hao; Sen Yang; Wei Li; Zhongwei Chen (Rock Mechanics and Rock Engineering, 2026)

Knockdown of Lcn2 alleviates pyroptosis in a neonatal rat model of necrotizing enterocolitis through IL-17A signaling pathway suppression - Shuyun Chen; Xiaobing Sun; Sen Xu; Zhenhua Yang; Rao Cui (Tissue and Cell, 2026)

The function of the alternative oxidase gene in the tolerance of Fusarium graminearum to azoxystrobin - Hao-Jie Sun; Yu-Liang Qin; Yi-Wen Feng; Ying-Ying Wang; Huan-Chen Zhai; Yang-Yong Lv; Yuan-Sen Hu; Shuai-Bing Zhang; Liang Huang (Pesticide Biochemistry and Physiology, 2026)

Seasonal dynamics of plankton networks and copepod selection strategies in the laver cultivation area of Haizhou Bay, China: based on sparse correlations for compositional data analysis - Sen Li; Hong Huang; Jinchen Yu; Tao Sun; Shuo Chen; Jin Zhou; Yunrong Shi; Peng Zhang; Jieqing Yang (Marine Environmental Research, 2026)

Oil-phase modulated molecular assembly in rice bran protein fibril-chitin nanofiber emulsion gels: Structural design strategy for synchronized fat replacement and sodium release optimization - Yao Feng; Yu Zhang; Kai Huang; Sen Li; Hongwei Cao; Zhenliang Sun; Xiao Guan (Food Research International, 2026)

Electronic modulation of nitride/hydroxide heterostructure for long-lasting urea oxidation reaction over 1000 h - Xian-Jun Niu; Guang-Sheng Qian; Yang Bai; Shen-Bing Sun; Lei Zhou; Wei-Yong Jiao; Ji-Sen Li (Chemical Engineering Journal, 2026)

Theoretical insights into anisotropic breathing in flexible MOFs via strategic functionalization for ultraefficient C2 hydrocarbon separation - Sen Liu; Zhe Sun; Bo Liao; Maohuai Wang; Shuxian Wei; Baojun Wei; Xiaoqing Lu (Chemical Engineering Journal, 2026)

Mechanistic effects of starch-lipid complexes formation on oat starch digestibility during roasting process - Wenhua Ma; Fan Yang; Binghua Sun; Xiaojie Qian; Sen Ma; Chong Liu; Xiaoxi Wang (Carbohydrate Polymers, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Enhanced norfloxacin oxidation with an Fe(VI)/peroxydisulfate-quinone process: iron species-driven multi-oxidation, quinone-based regulation, and density functional theory analysis - Xiao Luo; Yihan Li; Xiaoke Ma; Tapas Sen; Lin Zhao; Yongkui Yang; Peizhe Sun (Water Research, 2026)

Functional analysis of heat shock protein 70 genes in Tetranychus truncatus reveals their critical role in cross-tolerance to heat and acaricide stress - Qin-Zhe Sun; Lei Liu; Huan Liu; Xing Xiang; Li-Wen Song; Sen-Shan Wang (Pesticide Biochemistry and Physiology, 2026)

Seismic characterization of ancient lacustrine source-to-sink systems in a rift basin: The Bozhong Depression, Bohai Bay Basin, China - Xiaobo Zheng; Hongtao Zhu; Sen Li; Haifeng Yang; Zhiwei Zeng; Zhongheng Sun (Marine and Petroleum Geology, 2026)

Influence of pyrolysis on biomass structure: microscopic deformation patterns and chemical composition variations - Shao-Hua Sun; Jiang Wan; Hui-Chun Fu; Yong-Huan Sun; Feng Shao; De-Sen Ni; Jian-Jiang Lu (Fuel, 2026)

Phase-regulated colloidal FeS for controlled sulfidation and precise copper–arsenic separation under strongly acidic conditions - Xingfei Zhang; Wei Sun; Haisheng Han; Xianzhong Bu; Sen Wang; Xuewen Song; Chenglong Lu; Jiwei Xue; He Wan; Chonghui Zhang (Process Safety and Environmental Protection, 2025)

Research on effective trajectory planning, tracking, and reconstruction for USV formation in complex environments - Sen Han; Jiahao Sun; Lingxiao Yan; Shifeng Ding; Li Zhou (Ocean Engineering, 2025)

Recovery of rhenium from dust and waste acid generated from copper-molybdenum smelting: A critical review - Xingfei Zhang; Zihao Sun; Xianzhong Bu; Wei Sun; Haisheng Han; Xuewen Song; Sen Wang; Jiwei Xue; Chonghui Zhang (Minerals Engineering, 2025)

Green and low-toxicity deep eutectic solvents for the recovery of methanol and methyl acetate from wastewater: Phase behavior and mechanistic investigation - Jun Li; Sen Li; Renting Li; Suying Chu; Zhanhua Ma; Lanyi Sun (Journal of Environmental Chemical Engineering, 2025)

Photocatalytic of hydrogen peroxide production on chelating agent decorated zinc cadmium sulfide@halloysite hybrid - Sen Lin; Shiyong Sun; Jun Liu; Xiang Li; Haoming Tang; Lin Gong; Xingyun Yang (Journal of Environmental Chemical Engineering, 2025)

Role of particle size and roasted degree modulating the stability of oat milk - Wenhua Ma; Fangfang Cheng; Qin Liang; Xiaojie Qian; Saiwen Song; Binghua Sun; Sen Ma; Xiaoxi Wang (Food Research International, 2025)

Limited carbon sequestration potential despite enhanced productivity in groundwater-influenced hyper-arid ecosystems - Mengtao Ci; Xingming Hao; Sen Zhang; Fan Sun; Qixiang Liang; Xue Fan; Jingjing Zhang; Xuewei Li; Haibing Xiong (Journal of Hydrology, 2025)

Horizontally transferred NADAR genes contribute to immune defense of ladybird beetles against bacterial infection - Kun-Yu Yang; Yi-Fei Sun; Yuan-Sen Liang; Hao Li; Meng-Xue Qi; Zhaowei Wang; Luis Carlos Ramos Aguila; Li-Qun Cai; Hao-Sen Li; Hong Pang (Insect Biochemistry and Molecular Biology, 2025)

Mechanism of high intensity ultrasonic treatment combined with β-glucan affecting the structure of highland barley protein to improve the stability of highland barley milk - Hongwei Cao; Xiaotong Zhuang; Haojie Liu; Man Wang; Kai Huang; Hongdong Song; Sen Li; Yu Zhang; Zhenliang Sun; Xiao Guan (Food Hydrocolloids, 2025)

Snapping-induced electro-burst metamaterial for self-powered threshold monitoring - Sen Yan; Linchuan Zhao; Zhiqiang Meng; Ningning Song; Fubei Liu; Weijia Luo; Yongzheng Wen; Yifan Wang; Jingbo Sun; Lingling Wu; Ji Zhou (Engineering Structures, 2025)

Efficacy of a non-recombinant NADC34-like PRRSV-2 vaccine candidate against a recombinant NADC34-like PRRSV-2 isolate - Ming Qiu; Shuai Li; Meng Cui; Shuai Yang; Xiaoyang Zhu; Yifan Meng; Yanhan Lin; Hong Lin; Zhe Sun; Yuan Wang; Sen Jiang; Wanglong Zheng; et al. (Veterinary Microbiology, 2025)

The MYB transcription factor ClPC modulates petal color and chlorophyll accumulation in watermelon - Dongming Liu; Liming Zhang; Aofeng Hu; Dongling Sun; Yaxin Chen; Shixiang Duan; Yachen Liu; Junling Dou; Sen Yang; Huanhuan Niu; Wenkai Yan; Jianbin Hu; et al. (Plant Science, 2025)

Enhanced removal of Cr (VI) in constructed wetland with Fe-Ni-LDH-modified crayfish shell biochar: Performance, removal pathways and synergy mechanisms of substrate-microorganism - Wenshu Wang; Huazhen Wu; Junqi Sun; Chunyan Zhai; Jingxin Song; Deliang Chen; Guoxian Yang; Yile Dai; Sen Wang; Fanlong Kong (Journal of Hazardous Materials, 2025)

Synthesis of novel thiol-functionalized halloysite nanotube/ organophyllosilicate composite for efficient removal of aqueous U(VI) - Edward Opong Acheampong; Ke Wang; Haoming Tang; Sen Lin; Shiyong Sun (Journal of Environmental Chemical Engineering, 2025)

Detoxifying zinc oxide nanoparticles during sludge anaerobic digestion in the presence of polyferric sulfate - Yongkui Yang; Junxiang Huang; Sen Qu; Guangxue Wu; Yiwen Liu; Yifeng Ling; Peizhe Sun; Yingxin Zhao; Lin Zhao (Journal of Environmental Chemical Engineering, 2025)

Exploring the limit of Cu-based small-pore zeolite framework collapse during hydrothermal aging in NO abatement from diesel vehicle exhaust - Wenqing Ding; Yu Sun; Jinpeng Du; Zhongqi Liu; Jingjing Liu; Tongliang Zhang; Wenpo Shan; Xiaoyan Shi; Sen Xue; Xuewang Han; Yunbo Yu; Yulong Shan; et al. (Journal of Environmental Sciences, 2025)

Characterization and efficacy of α-glucosidase inhibitory peptides from enzymatically hydrolyzed Peanut meal - Sen Zhou; Zhiran Zhang; Shengxin Li; Mengkai Liu; Ziyan Zhang; Na Wang; Jie Sun (Food Research International, 2025)

Molecular docking screening of endogenous protease inhibitors in sea bass (Lates calcarifer) and in vitro validation of their inhibitory efficacy - Run-Jian Gao; Lu Sun; Sen-Di Zhou; Yu-Meng Liu; Wei-Qiang Qiu; Sheng-Ping Yang; Yun-Fang Qian (Food Bioscience, 2025)

Enhancing the formation rate and level of oat globulin fibrils by microwave heating: Elucidation of potential mechanisms - Mengdi Cai; Hongwei Cao; Sen Li; Hongdong Song; Yu Zhang; Kai Huang; Man Wang; Zhenliang Sun; Xiao Guan (Food Hydrocolloids, 2025)

High-throughput real-time detection of sepsis inflammatory biomarker proteins in clinical samples using metasurface plasmon resonance biosensors - Jing Wu; Youqian Chen; Liping Huang; Yuhan Sun; Jingjing Zhao; Xiaoyang Cheng; Ruiwen Sun; Hanlin Zhou; Yue Shu; Wen Li; Wenhong Zhang; Wei Liu; et al. (Chemical Engineering Journal, 2025)

Genetic and histological characterization of a dwarf mutant in melon (Cucumis melo L.) reveals potential for breeding semi-dwarf cultivars - Zhuoxi Han; Wanning Zheng; Yang Li; Qingqing Ou; Haipeng Zhao; Han Zhao; Ju Xu; Sen Chai; Xueyong Yang; Zhonghua Zhang; Jinjing Sun (Theoretical and Applied Genetics, 2025)

The history of wheat evolution drives rhizosphere microbiome succession and their functional adaptation - Xuming Sun; Chenhang Luo; Xiaohong Niu; Xiao Wei; Yun Jiang; Sen Du; Gehong Wei; Duntao Shu (Plant and Soil, 2025)

Impact of environmental attractiveness and socio-economic status on residents’ green space visitation in northeastern China - Xin Yang; Jinchen Wang; Yinsheng Zhang; Ruying Fang; Yifan Sun; Sen Li (Urban Forestry & Urban Greening, 2025)

Designing food matrix structure by adjusting the ratio of soluble/insoluble wheat bran dietary fiber to mitigate the inhibition on wheat protein digestion: Application in noodles - Lingfang Zhang; Qianyi Jiang; Binghua Sun; Xiaoxi Wang; Sen Ma (Food Chemistry, 2025)

Influencing the retrogradation properties of potato mash through multi-scale structural modifications mediated by enzymatic hydrolysis forms - Hongwei Cao; Mengting Huang; Zhenhao Liu; Kai Huang; Man Wang; Hongdong Song; Sen Li; Yu Zhang; Zhenliang Sun; Xiao Guan (Food Chemistry, 2025)

Modulating band structure of MoO3 via W-doped for enhanced photo-induced charge transfer and SERS detection - Hongwen Cao; Yunpeng Cao; Jia He; Xin Xie; Zhijun Wang; Sen Sun; Rui Zhong; Lei Sun; Yihan Wang; Kun Zhang (Chemical Engineering Journal, 2025)

Dietary protease inclusion with activity after pelleting affects growth performance, digestive enzyme activity, nutrient sensing signaling pathway and intestinal health of larval largemouth bass (Micropterus salmoides) - Nihe Zhang; Ye Gong; Runwei Miao; Zeqiang Sun; Sen Zhang; Xuxiong Huang; Naisong Chen; Songlin Li (Aquaculture, 2025)

Spatial response and optimisation partitioning of the impact of marine industry development on ecological vulnerability—A case study of Jiangsu coastal counties - Hui Guo; Sen Wang; Wei Sun (Ocean & Coastal Management, 2025)

Screening of immunogenic antigens from scuticociliate in Takifugu rubripes, and the development and evaluation of subunit vaccines - Xiaohang Wang; Sen Wang; Xinpeng Ni; Gengtong Zhao; Qingmeihui Sun; Ziyi Zhang; Meili Pan; Ruijun Li (Fish & Shellfish Immunology, 2025)

Viral Diversity Mediates Carbon Allocation for Ecosystem Multifunctionality Across Biomes - Sen Li; Weigen Huang; Bin Ma; Longlong Xia; Han Hu; Yishen Sun; Haowei Ni; Mengting Maggie Yuan; Jizhong Zhou; Jiabao Zhang; Yuting Liang (Global Change Biology, 2025)
Viral diversity is essential for regulating the stability of ecosystem function by modulating the biochemical cycles via alterations in the survival and metabolic processes of host organisms. However, how viral survival strategies impact ecosystem function remains unresolved. Here, we analyzed 1824 metagenomes from soils across eight biomes, revealing that lytic viruses constituted a dominant proportion (88%) of the viral communities, with Siphoviridae (35.34%) being the most abundant lytic viral group. Viral communities significantly impacted soil organic carbon dynamics, while ecosystem multifunctionality was notably influenced by microbial necromass carbon, microbial biomass carbon, and various environmental factors. Microbial carbon use efficiency was the primary driver of ecosystem multifunctionality, with significant modulation by lytic and lysogenic viral communities, and lytic viruses contributed more directly to ecosystem multifunctionality (3%) compared to lysogenic viruses (1%). Our study underscores the pivotal role of viral communities, particularly lytic viruses, in shaping global carbon dynamics and ecosystem function, thereby providing a novel framework for future carbon management.

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Dynamic changes of stomatal distribution, protein structural and liquor properties of oat dough during the fermentation process affected by moderately gelatinized oat flour - Xiaojie Qian; Lingfang Zhang; Binghua Sun; Sen Ma; Chong Liu; Xiaoxi Wang (Food Research International, 2025)

Rice bran protein fibril and chitin nanofiber complexes as a new material for fat substitution and saltiness enhancement - Yao Feng; Yu Zhang; Kai Huang; Sen Li; Hongwei Cao; Pengxiao Zhang; Man Wang; Zhenliang Sun; Xiao Guan (Food Chemistry, 2025)

A fracture mechanics approach to investigating the crunchy texture of konjac glucomannan gels through imitative chewing tests - Zhenjun Liu; Chunan Sun; Sen Hu; Guohua Zhao; Yun Zhou (Food Hydrocolloids, 2025)

Ultra-stable CO2-aqueous foams for carbon sequestration and internal mineralization in cellular cements - Dingqiang Fan; Xue-Sen Lv; Jian-Xin Lu; Rui Yu; Wei She; Juhyuk Moon; Takafumi Noguchi; Chi Sun Poon (Chemical Engineering Journal, 2025)

Effectively mitigated eutrophication risk by strong biological carbon pump (BCP) effect in karst reservoirs - Wenke Zhang; Wanfa Wang; Sen Xu; Qingqing Sun; Wenhong Shi; Jiayi Man; Shengde Yu; Yujing Yang; Wenxin Wu; Xia Hu; Qixin Wu; Pan Wu; et al. (Water Research, 2025)

A lightweight YOLO network using temporal features for high-resolution sonar segmentation - Sen Gao; Wei Guo; Gaofei Xu; Ben Liu; Yu Sun; Bo Yuan (Frontiers in Marine Science, 2025)
Introduction High-resolution sonar systems are critical for underwater robots to obtain precise environmental perception. However, the computational demands of processing sonar imagery in real-time pose significant challenges for autonomous underwater vehicles (AUVs) operating in dynamic environments. Current segmentation methods often struggle to balance processing speed with accuracy. Methods We propose a novel YOLO-based segmentation framework featuring: (1) A lightweight backbone(ghostnet) network optimized for sonar imagery processing (2) A bypass BiLSTM network for temporal feature learning across consecutive frames. The system processes non-keyframes by predicting semantic vectors through the trained BiLSTM model, selectively skipping computational layers to enhance efficiency. The model was trained and evaluated on a high-resolution sonar dataset collected using an AUV-mounted Oculus MD750d multibeam forward-looking sonar in two distinct underwater environments. Results Implementation on Nvidia Jetson TX2 demonstrated significant performance improvements. (1) Processing latency reduced to 87.4 ms (keyframes) and 35.3 ms (non-keyframes)(2)Maintained competitive segmentation accuracy compared to conventional methods and achieved low latency. Discussion The proposed architecture successfully addresses the speed-accuracy trade-off in sonar image segmentation through its innovative temporal feature utilization and computational skipping mechanism. The significant latency reduction enables more responsive AUV navigation without compromising perception quality. The newly introduced dataset fills an important gap in high-resolution sonar benchmarking. Future work will focus on optimizing the keyframe selection algorithm and expanding the dataset to include more complex underwater scenarios.

Novel tetracycline-degrading enzymes from the gut microbiota of black soldier fly: Discovery, performance, degradation pathways, mechanisms, and application potential - Yaxin Pei; Aojie Lei; Mengyao Wang; Mengxiao Sun; Sen Yang; Xinyu Liu; Liangwei Liu; Hongge Chen (Journal of Hazardous Materials, 2025)

Methane hydrate formation kinetics and structure information in the presence of cyclopentane under different reaction evolution - Wen-Zhe Sun; Hai-Long Liu; Kai Zhang; Xu-Ke Ruan; Yi-Song Yu; Xiao-Sen Li (Chemical Engineering Journal, 2025)

Linking prokaryotic life-history strategies to soil organic carbon stability in semi-arid orchard with cover crops - Yidan Liu; Zhidi Chen; Luhan Li; Yangping Sun; Xiao Hu; Xike Zhang; Sanfeng Chen; Sen Du; Wenfeng Chen; Gehong Wei; Chun Chen (CATENA, 2025)

Dynamic regulation of iturin production via reconstructing the quorum-sensing system ComQXPA in Bacillus subtilis - Guojun Wu; Chenyue Yin; Jie Zheng; Mengxi Wang; Dyaaaldin Abdalmegeed; Fengmin Zhang; Shengwei Sun; Sen Sun; Yuting Shao; Zhihong Xin (World Journal of Microbiology and Biotechnology, 2025)

The capsid protein p72 specific mAb and the corresponding novel epitope based ELISAs for detection of ASFV infection - Jiajia Zhang; Ziyan Sun; Shaohua Sun; Kaili Zhang; Dafu Deng; Ping He; Pingping Zhang; Nengwen Xia; Sen Jiang; Wanglong Zheng; Francois Meurens; Jianzhong Zhu (Veterinary Microbiology, 2025)

A comprehensive omics resource and genetic tools for functional genomics research and genetic improvement of sorghum - Chengxuan Chen; Fengyong Ge; Huilong Du; Yuanchang Sun; Yi Sui; Sanyuan Tang; Zhengwei Shen; Xuefeng Li; Huili Zhang; Cuo Mei; Peng Xie; Chao Li; et al. (Molecular Plant, 2025)

Characteristics of intestinal microbial communities and occurrence of antibiotic resistance genes during degradation of antibiotic mycelial residues by black soldier fly (Hermetia illucens L.) larvae - Yaxin Pei; Mengxiao Sun; Minghui Wang; Aojie Lei; Xinyu Liu; Hongge Chen; Sen Yang (Environmental Pollution, 2025)

PWP1 transcriptionally regulates p53, modulating apoptosis and cell cycle to promote gastric cancer progression - Mingrui Jiang; Sen Wang; Jin Ji; Shantanu Baral; Qiannan Sun; Yong Wang; Bin Liu; Jun Ren; Wei Wang; Daorong Wang (Apoptosis, 2025)

A nucleocapsid monoclonal antibody based sandwich ELISA for the general detection of both PRRSV-2 and PRRSV-1 - Shaohua Sun; Kaili Zhang; Jiajia Zhang; Ping He; Pingping Zhang; Dafu Deng; Chenglin Chi; Sen Jiang; Wanglong Zheng; Nanhua Chen; Jianzhong Zhu (Veterinary Microbiology, 2025)

Aerobic composting with hydrothermal carbonization aqueous phase conditioning: Stabilized active gaseous nitrogen emissions - Yuanyuan Feng; Haijun Sun; Sen Chen; Wenping Xie; Hongmei Jin; Yanfang Feng; Gerrard Eddy Jai Poinern; Lihong Xue (Journal of Hazardous Materials, 2025)

Subaxillary implantation of mesenchymal stem cell spheroids is a novel therapy for myocardial ischemia reperfusion injury - Yihai Liu; Sen Yan; Mingyue Wu; Yuanyuan Xie; Jingyi Sheng; Xuan Sun; Lina Kang; Biao Xu; Ning Gu (Chemical Engineering Journal, 2025)

Mixed vector autoregression and GARCH–Copula approach for long-term streamflow probabilistic forecasting in a multisite system - Saijin Ji; Bin Xu; Yu Sun; Ran Mo; Sen Wang; Peng Lu (Stochastic Environmental Research and Risk Assessment, 2025)

Interspecific predation of a native herbivore facilitates colonization by fall armyworms, Spodoptera frugiperda - Yingying Song; Kangwen Sun; Sen Guo; Zhaoke Dong; Ritao Qu; Hongying Cui; Wenxiu Guo; Baohua Ye; Lili Li; Yuyong Liang; Xingyuan Men (Journal of Pest Science, 2025)

Red princess of the Silk Road - the first-and-only known case of cinnabar-stained teeth in antiquity from the Iron Age Western Regions (202BCE − 8CE) - Sen You; Meng Ren; Li Sun; Anqi Wang; Long Wang; Quanchao Zhang; Qian Wang (Archaeological and Anthropological Sciences, 2025)

COLREGs-Compliant autonomous collision avoidance and improved adaptive LOS-based motion control for USVs in complex waters - Ke Liu; Shifeng Ding; Lingxiao Yan; Jiahao Sun; Shidi Wu; Sen Han; Fang Li; Li Zhou (Ocean Engineering, 2025)

Hybrid trajectory planning and tracking for automatic berthing: A grid-search and optimal control integration approach - Sen Han; Lingxiao Yan; Jiahao Sun; Shifeng Ding; Fang Li; Feng Diao; Li Zhou (Ocean Engineering, 2025)

3D-Printed porous MnO2/Carbon composites synthesized via fast joule heating for energy storage electrodes - Jun Cao; Chunjie Yan; Qi Sun; Xiaoyan Zhu; Sen Zhou; Ziming Song; Zhigang Wang; Heng Deng (Chemical Engineering Journal, 2025)

Hypoxia-adaptive penetration enhanced nanomedicine regulating cell–internalization ability enabling the uniform distribution within tumors - Sen Liu; Dongsheng Jiang; Sumeng Qian; Zhendong Ren; Jing Sun; Wei Ye; Jie Zhao (Chemical Engineering Journal, 2025)

Co-application of hydrothermal carbonization aqueous phase and biogas slurry reduced ammonia volatilization in paddy - Yimeng Wang; Haijun Sun; Yahui Ji; Yuanyuan Feng; Sen Chen; Shudong Ding; Yaxin Ma; Bingyu Wang; Yanfang Feng; Huifang Xie; Lihong Xue (Journal of Environmental Management, 2025)

Unveiling shape-dependent intrinsic activity of cadmium sulfide (CdS) for photocatalytic uranium(VI) reduction - Yihao Quan; Sen Lu; Qingliang Wang; Hongqiang Wang; Eming Hu; Xinnan Wang; Jiacheng Bao; Xin Sun; Kai Li; Ping Ning (Chemical Engineering Journal, 2025)

Microwave-Assisted Linear Cutting of Sandstone with a Conical Pick: Experimental Study - Yixin Zhao; Chuncheng Sun; Yirui Gao; Sen Gao; Jinbao Guo; Ronghuan Xie; Xiaodong Guo (Rock Mechanics and Rock Engineering, 2025)

Enzymatically cross-linked arabinoxylan hydrogel: Effect of glucose oxidase on the gel characteristics and oral colon-targeted delivery for Naja atra neurotoxin - Nianxia Sun; Fuping Zhuang; Chongyang Wang; Jing Wu; Sen Liu; Wenli Chang; Weimin Jin; Dianlei Wang (Journal of Food Engineering, 2024)

Predicting straw drinking ability of liquid foods by pipe-flow rheometry - Sen Hu; Chunan Sun; Wei Wei; Lin Lei; Guohua Zhao; Yun Zhou (Food Research International, 2024)

Interfacial Mo-N bonding enhancement of N-doped carbon nanosheets-stabilized ultrafine MoS2 enable ultrafast and durable sodium ion half/full batteries - Dongfei Sun; Sen Lin; Shengxu Kuai; Tiantian Zhang; Lei Liu; Jingxin Zhao; Xiaozhong Zhou; Wenwen Liu; Bingang Xu (Chemical Engineering Journal, 2024)

Stomatin-like protein 2 promotes cell proliferation and survival under 5-Fluorouracil stress in hepatocellular carcinoma - Xiaoqi Li; Yahui Zheng; Kangkang Yu; Sen Hou; Huxiao Cui; Ruiqi Yin; Yu Zhou; Qingfeng Sun; Jubo Zhang; Chong Huang (Molecular Biology Reports, 2024)

Synthesis of Fe-ZSM-5 zeolite from high iron-containing palygorskite with peroxidase-like catalytic performance - Fengya Ran; Meng He; Shiyong Sun; Rui Lv; Sen Lin; Ke Wang; Yevgeny Aleksandrovich Golubev; Olga Borisovna Kotova; Elena Leonidovna Kotova (Applied Clay Science, 2024)

Automatic unberthing for underactuated unmanned surface vehicle: Model-based planning and control approaches in constricted harbors - Sen Han; Lingxiao Yan; Jiahao Sun; Shifeng Ding; Fang Li; Li Zhou (Ocean Engineering, 2024)

Protein digestibility in wheat noodles: The inhibitory effect and its mechanism of wheat bran dietary fiber - Lingfang Zhang; Xiaojie Qian; Binghua Sun; Shuzhen Yang; Xiaoxi Wang; Sen Ma (Journal of Cereal Science, 2024)

Versatile and efficient mammalian genome editing with Type I-C CRISPR System of Desulfovibrio vulgaris - Pan Li; Dingcai Dong; Fei Gao; Yuyang Xie; Honglin Huang; Siwei Sun; Zhao Ma; Cheng He; Jinsheng Lai; Xuguang Du; Sen Wu (Science China Life Sciences, 2024)

Prediction of Bone Remodeling in Rat Caudal Vertebrae Based on Fluid-Solid Coupling Simulation - Sen Zhao; Yan Gao; Huijie Leng; Lianwen Sun; Bo Huo (Annals of Biomedical Engineering, 2024)

Underwater image restoration via attenuated incident optical model and background segmentation - Sen Lin; Yuanjie Sun; Ning Ye (Frontiers in Marine Science, 2024)
Underwater images typically exhibit low quality due to complex imaging environments, which impede the development of the Space-Air-Ground-Sea Integrated Network (SAGSIN). Existing physical models often ignore the light absorption and attenuation properties of water, making them incapable of resolving details and resulting in low contrast. To address this issue, we propose the attenuated incident optical model and combine it with a background segmentation technique for underwater image restoration. Specifically, we first utilize the features to distinguish the foreground region of the image from the background region. Subsequently, we introduce a background light layer to improve the underwater imaging model and account for the effects of non-uniform incident light. Afterward, we employ a new maximum reflection prior in the estimation of the background light layer to achieve restoration of the foreground region. Meanwhile, the contrast of the background region is enhanced by stretching the saturation and brightness components. Extensive experiments conducted on four underwater image datasets, using both classical and state-of-the-art (SOTA) algorithms, demonstrate that our method not only successfully restores textures and details but is also beneficial for processing images under non-uniform lighting conditions.

Health benefits of saponins and its mechanisms: perspectives from absorption, metabolism, and interaction with gut - Yu Zhang; Ruojie Hao; Junda Chen; Sen Li; Kai Huang; Hongwei Cao; Mohamed A. Farag; Maurizio Battino; Maria Daglia; Esra Capanoglu; Fan Zhang; Qiqi Sun; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Integrated transcriptome and metabolome profiles reveal the regulatory molecular mechanisms of meat quality in pasture-fed goose - Qasim Ali; Boshuai Liu; Shaokai La; Umar Farooq; Yao Han; Mengqi Liu; Yan Zhang; Defeng Li; Zhichang Wang; Hao Sun; Yalei Cui; Sen Ma; et al. (Food Bioscience, 2024)

Optimizing radiation capture in machine-harvested cotton: A functional-structural plant modelling approach to chemical vs. manual topping strategies - Shenghao Gu; Shuai Sun; Xuejiao Wang; Sen Wang; Mingfeng Yang; Jie Li; Paerhati Maimaiti; Wopke van der Werf; Jochem B. Evers; Lizhen Zhang (Field Crops Research, 2024)

A novel dual functional gradient Zn(O,S)/Mg electron-selective contact for dopant‐free silicon solar cells with efficiencies approaching 21 % - Junfeng Zhao; Zhongqing Zhang; Shengpeng Xie; Fangfang Liu; Yongtai Zhen; Sen Li; Wenzhu Liu; Anjun Han; Liping Zhang; Zhengxin Liu; Yun Sun; Wei Liu (Chemical Engineering Journal, 2024)

Specific adsorption of antiviral drugs on ionic liquid-modified metal–organic framework: Adsorption behavior, mechanism, and DFT analysis - Yihan Li; Lin Zhao; Daying Chen; Tapas Sen; Guining Lu; Jiashu Liu; Xiaodong Du; Peizhe Sun; Yongkui Yang (Chemical Engineering Journal, 2024)

The survival, gene expression, and DNA methylation of Paralichthys olivaceus impacted by the decay of green tide and bacterial infection in both laboratory and field simulation experiments - Jie Ma; Kunpeng Shi; Weijun Zhang; Sen Han; Zhendong Wu; Muyuan Wang; Haibo Zhang; Jiacheng Sun; Ningning Wang; Mengyang Chang; Xiaoyong Shi; Suxu Tan; et al. (Science of The Total Environment, 2024)

Volatomic differences among Vitis amurensis cultivars and its hybrids with V. vinifera revealed the effects of genotype, region, and vintage on grape aroma - Ming-Yu Li; Xuan-Xuan Pei; Ning Shi; Yi-Ming Yang; Shu-Tian Fan; Yan-Feng Sun; Qing-Sen Kong; Chang-Qing Duan; Keji Yu; Jun Wang (Food Research International, 2024)

Impact of roasted oat flour on the gas cell structure of steamed oat cake and its underlying mechanism - Binghua Sun; Xiaojie Qian; Sen Ma; Chong Liu; Xiaoxi Wang (Food Hydrocolloids, 2024)

The regulation effect of urban green space on air particulate matter concentration under different matrices in Xi'an city - Bo Jiang; Shiyu Fan; Chang Sun; Sen Mu; Tian Gao; Ling Qiu (Air Quality, Atmosphere & Health, 2024)

No increase of soil wind erosion with the establishment of center pivot irrigation system in Mu-Us sandy land - Jie Liao; Fei Peng; Wenping Kang; Xiaojie Chen; Jianbo Sun; Ben Chen; Yu Xia; Heqiang Du; Sen Li; Xiang Song; Tao Wang (Science of The Total Environment, 2024)

Dynamic response of allelopathic potency of Taxus cuspidata Sieb. et Zucc. mediated by allelochemicals in Ficus carica Linn. root exudates - Qianqian Li; Yifan Zhou; Wenxue Sun; Bin Qiao; Jiabo Cheng; Sen Shi; Chunjian Zhao; Chunying Li (Science of The Total Environment, 2024)

Abnormal Innervation, Demyelination, and Degeneration of Spiral Ganglion Neurons as Well as Disruption of Heminodes are Involved in the Onset of Deafness in Cx26 Null Mice - Yue Qiu; Le Xie; Xiaohui Wang; Kai Xu; Xue Bai; Sen Chen; Yu Sun (Neuroscience Bulletin, 2024)

Thermal fracturing of anthracite under low-energy microwave irradiation: An experimental study - Yirui Gao; Yixin Zhao; Sen Gao; Zhuang Sun; Xiaoliang Wang; Hao Wang (International Journal of Rock Mechanics and Mining Sciences, 2024)

Development of visual detection of African swine fever virus using CRISPR/LwCas13a lateral flow strip based on structural protein gene D117L - Desheng Zhang; Sen Jiang; Nengwen Xia; Jiajia Zhang; Anjing Liu; Dafu Deng; Chenyang Zhang; Yuxin Sun; Nanhua Chen; Xilong Kang; Zhiming Pan; Wanglong Zheng; et al. (Veterinary Microbiology, 2024)

A study on ice resistance prediction based on deep learning data generation method - Qianyang Sun; Jiaming Chen; Li Zhou; Shifeng Ding; Sen Han (Ocean Engineering, 2024)

Expression and function identification of senescence-associated genes under continuous drought treatment in grapevine (Vitis vinifera L.) leaves - You-Mei Li; Xuan-Si Tang; Meng-Hao Sun; Hong-Xing Zhang; Zhao-Sen Xie (Physiology and Molecular Biology of Plants, 2024)

Tetrabromobisphenol A and hexabromocyclododecane in sediments from the Zhujiang (Pearl) River Estuary and South China Sea - Chuyue Long; Weiyan Yang; Jiaxun Lu; Yuanyue Cheng; Ning Qiu; Sen Du; Li Zhang; Shejun Chen; Yuxin Sun (Acta Oceanologica Sinica, 2024)

Intrinsic microbial temperature sensitivity and soil organic carbon decomposition in response to climate change - Sen Li; Manuel Delgado‐Baquerizo; Jixian Ding; Han Hu; Weigen Huang; Yishen Sun; Haowei Ni; Yanyun Kuang; Mengting Maggie Yuan; Jizhong Zhou; Jiabao Zhang; Yuting Liang (Global Change Biology, 2024)
Soil microbes are essential for regulating carbon stocks under climate change. However, the uncertainty surrounding how microbial temperature responses control carbon losses under warming conditions highlights a significant gap in our climate change models. To address this issue, we conducted a fine‐scale analysis of soil organic carbon composition under different temperature gradients and characterized the corresponding microbial growth and physiology across various paddy soils spanning 4000 km in China. Our results showed that warming altered the composition of organic matter, resulting in a reduction in carbohydrates of approximately 0.026% to 0.030% from humid subtropical regions to humid continental regions. These changes were attributed to a decrease in the proportion of cold‐preferring bacteria, leading to significant soil carbon losses. Our findings suggest that intrinsic microbial temperature sensitivity plays a crucial role in determining the rate of soil organic carbon decomposition, providing insights into the temperature limitations faced by microbial activities and their impact on soil carbon‐climate feedback.

Hydraulic fracture initiation and propagation in deep coalbed methane reservoirs considering weak plane: CT scan testing - Qingshan Ren; Cun Zhang; Guangjie Wu; Hongwei Zhang; Sen Gao; Zhuang Sun; Yirui Gao (Gas Science and Engineering, 2024)

Machine-learning-assisted hydrogen adsorption descriptor design for bilayer MXenes - Weizhi Tian; Gongchang Ren; Yuanting Wu; Sen Lu; Yuan Huan; Tiren Peng; Peng Liu; Jiangong Sun; Hui Su; Hong Cui (Journal of Cleaner Production, 2024)

Catalytic co-pyrolysis of coffee grounds and polyethylene: A comparison of HZSM-5 and HY - Jiawei Fu; Sen Lin; Bin Cai; Jiayu Liang; Zhibin Chen; Fatih Evrendilek; Sheng Zhong; Zuoyi Yang; Chunxiao Yang; Yao He; Shuiyu Sun; Jingyong Liu (Fuel, 2024)

Cotton crop transpiration reveals opportunities to reduce yield loss when applying defoliants for efficient mechanical harvesting - Yongfan Chen; Jochem B. Evers; Mingfeng Yang; Xuejiao Wang; Zeshan Zhang; Shuai Sun; Yutong Zhang; Sen Wang; Fen Ji; Dao Xiang; Jie Li; Chunrong Ji; et al. (Field Crops Research, 2024)

Pre-mating nitenpyram exposure in male mice leads to depression-like behavior in offspring by affecting tryptophan metabolism in gut microbiota - Sen Yan; Wei Sun; Sinuo Tian; Zhiyuan Meng; Jinling Diao; Zhiqiang Zhou; Li Li; Wentao Zhu (Journal of Environmental Sciences, 2024)

Enzymatic hydrolysis of oat core flour improves physiochemical and sensory behaviors for oat milk - Min Zhang; Kai Huang; Jun Lu; Anni Lu; Xiao Guan; Yu Zhang; Sen Li; Hongdong Song; Hongwei Cao; Zhu Sun; Zhiquan Yu (Journal of Cereal Science, 2024)

The pH adjustment of Vitis amurensis dry red wine revealed the evolution of organic acids, volatomics, and sensory quality during winemaking - Meng-Bo Tian; Rui-Qi Hu; Zhao-Long Liu; Ning Shi; Hao-Cheng Lu; Chang-Qing Duan; Jun Wang; Yan-Feng Sun; Qing-Sen Kong; Fei He (Food Chemistry, 2024)

The role of lipids in determining the gas cell structure of gluten-free steamed oat cake - Xiaojie Qian; Binghua Sun; Sen Ma; Chong Liu; Xiaoxi Wang (Food Hydrocolloids, 2024)

Peroxymonosulfate activation by walnut shell activated carbon supported nano zero-valent iron for the degradation of tetracycline: Performance, degradation pathway and mechanism - Pingping Duan; Fanlong Kong; Xiuzheng Fu; Zhijie Han; Guangwei Sun; Zhengda Yu; Sen Wang; Yuqian Cui (Environmental Research, 2024)

Mechanism of propylene effect on the NH3-SCR performance of Cu-SSZ-13 catalyst - Wenqing Ding; Yu Sun; Jingjing Liu; Sen Xue; Xuewang Han; Zidi Yan; Yunbo Yu; Yulong Shan; Hong He (Chemical Engineering Journal, 2024)

Bifidobacterium mediate gut microbiota-remedied intestinal barrier damage caused by cyproconazole in zebrafish (Danio rerio) - Xiaoxuan Sun; Sinuo Tian; Sen Yan; Wei Sun; Jiyan Miao; Yifan Yue; Shihang Han; Shiran Huang; Ning Xu; Jinling Diao; Zhiqiang Zhou; Wentao Zhu (Science of The Total Environment, 2024)

Multi-omics and gut microbiome: Unveiling the pathogenic mechanisms of early-life pesticide exposure - Yifan Yue; Xiaoxuan Sun; Sinuo Tian; Sen Yan; Wei Sun; Jiyan Miao; Shiran Huang; Jinling Diao; Zhiqiang Zhou; Wentao Zhu (Pesticide Biochemistry and Physiology, 2024)

Construction of copper-manganese based aminoclays with significant laccase-like activity and its prominent degradation performance towards bisphenol A - Yifan Zeng; Shiyong Sun; Rui Lv; Ke Wang; Yevgeny Aleksandrovich Golubev; Sen Lin; Faqin Dong; Elena Leonidovna Kotova; Olga Borisovna Kotova (Journal of Environmental Chemical Engineering, 2024)

A new approach to extract the upright maize straw from Sentinel-2 satellite imagery using new straw indices - Jingping Zhou; Xiaohe Gu; Cuiling Liu; Wenbiao Wu; Yuchun Pan; Qian Sun; Sen Zhang; Xuzhou Qu (Computers and Electronics in Agriculture, 2024)

Fluctuating redox conditions accelerate the electron storage and transfer in magnetite and production of dark hydroxyl radicals - Dan Li; Jieyi Sun; Yibo Fu; Wentao Hong; Heli Wang; Qian Yang; Junhong Wu; Sen Yang; Jianhui Xu; Yunfei Zhang; Yirong Deng; Yin Zhong; et al. (Water Research, 2024)

Study on spray cooling characteristics of dry ice particles for IGBT in high-speed trainsfrEtude des caractéristiques de refroidissement par pulvérisation des particules de glace sèche pour l'igbt dans le train à grande vitesse - Jinghong Ning; Ziliang Ren; Luyao Sun; Zhipeng Song; Sen Zhu; Xue Gao (International Journal of Refrigeration, 2024)

Kinetics studies of methane hydrate formation and dissociation in the presence of cyclopentane - Yi-Song Yu; Wen-Zhe Sun; Chang Chen; Xiao-Sen Li; Zhao-Yang Chen (Fuel, 2024)

Construction of amidoxime-functionalized magnetic hydroxyapatite with enhanced uranium extraction performance from aqueous solution and seawater - Yan Wang; Yueyong Jiang; Yong Zhang; Xiaolin Liu; Sen Sun; Shiyi Qin; Jiaqi Huang; Bowei Chen (Chemosphere, 2023)

3D superhydrophobic lightweight foam concrete designed via in-situ foaming and self-assembled silicone microfilms - Xue-Sen Lv; Wen-Xiang Cao; M.H.N. Yio; Jian-Xin Lu; Chi Sun Poon (Chemical Engineering Journal, 2023)

Surfactin inhibits Fusarium graminearum by accumulating intracellular ROS and inducing apoptosis mechanisms - Chen Liang; Xu Xi-xi; Sun Yun-xiang; Xin Qiu-hua; Lv Yang-yong; Hu Yuan-sen; Bian Ke (World Journal of Microbiology and Biotechnology, 2023)

Intrinsic peroxidase-like clay mineral nanozyme-triggered cascade bioplatform with enhanced catalytic performance - Ke Wang; Shiyong Sun; Yevgeny Aleksandrovich Golubev; Sen Lin; Jin Liu; Faqin Dong; Elena Leonidovna Kotova; Olga Borisovna Kotova (Applied Clay Science, 2023)

Improved functionality and safety of peptides by the formation of peptide-polyphenol complexes - Duanquan Lin; Le-Chang Sun; Wei-Sen Huo; Ling-Jing Zhang; Yu-Lei Chen; Song Miao; Min-Jie Cao (Trends in Food Science & Technology, 2023)

In vitro starch digestibility of maize flour and maize extruded noodles based on different particle-size effects - Rui Ge; Xiaojie Qian; Binghua Sun; Sen Ma; Xiaoxi Wang (Journal of Cereal Science, 2023)

Characterization of atmospheric mercury from mercury-added product manufacturing using passive air samplers - Qing Luo; Yuxuan Ren; Zehang Sun; Yu Li; Bing Li; Sen Yang; Wanpeng Zhang; Frank Wania; Yuanan Hu; Hefa Cheng (Environmental Pollution, 2023)

Construction of polydopamine-functionalized phosphate-intercalated Mg Fe layered double hydroxide for efficient removal of U(VI) - Yan Wang; Yong Zhang; Xiaolin Liu; Sen Sun; Shiyi Qin; Jiaqi Huang; Bowei Chen (Journal of Water Process Engineering, 2023)

Evaluating the impact of the humic acid amendment on antibiotic resistance genes reduction and product quality during swine manure composting - Yousif Abdelrahman Yousif Abdellah; Hong-Yu Chen; Shan-Shan Sun; Xi Yang; Yu-Sen Luo; Ayodeji Bello; Taha Ahmed Mohamed; Rong-Jie Ren; Wan-Ting Li; Rashid Mohamed Ahmed; Rui-Long Wang (Journal of Environmental Chemical Engineering, 2023)

Hyperspectral estimation of maize (Zea mays L.) yield loss under lodging stress - Qian Sun; Xiaohe Gu; Liping Chen; Xuzhou Qu; Sen Zhang; Jingping Zhou; Yuchun Pan (Field Crops Research, 2023)

Crop cultivar mixtures stabilize productivity, partly via facilitation, when conditions are less benign - Ye Su; Rui-Peng Yu; Hua-Sen Xu; Jian-Hao Sun; Jian-Hua Zhao; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (Field Crops Research, 2023)

Hydrothermal carbonization aqueous phase promotes nutrient retention and humic substance formation during aerobic composting of chicken manure - Haijun Sun; Sen Chen; Ning Zhu; Paramsothy Jeyakumar; Jixiang Wang; Wenping Xie; Yanfang Feng (Bioresource Technology, 2023)

Carvacrol exhibits direct antifungal activity against stem-end rot disease and induces disease resistance to stem-end rot disease in kiwifruit - Tingting Mi; Donglan Luo; Jiangkuo Li; Guangfan Qu; Yanzheng Sun; Sen Cao (Physiological and Molecular Plant Pathology, 2023)

An R2R3-MYB Transcription Factor CmMYB42 Improves Low-Nitrogen Stress Tolerance in Chrysanthemum - Rui Ma; Sen Yang; Yanhong Liu; Xia Sun; Wenli Wang; Chengshu Zheng (Journal of Plant Growth Regulation, 2023)

Quantitative estimates of Holocene precipitation from aeolian sand-palaeosol sequences across the Ordos Plateau, northern China, based on surface soil geochemistry - Bing Liu; Hui Zhao; Heling Jin; Aimin Liang; Aijun Sun; Xiaomei Zhang; Caixia Zhang; Jianhui Jin; Hongyu Yang; Sen Li (CATENA, 2023)

Source analysis of metals in the tea plant using linear correlation analysis combined with a lead-strontium isotope tracer - Yan Cong; Rui-lian Yu; Yu Yan; Bo-sen Weng; Gong-ren Hu; Jing-wei Sun; Jian-yong Cui; YanYan; Yao-yi Huang (CATENA, 2023)

Flexible Riser Tensile Armor Modelling Method and Application to Fatigue Analysis - Ning Zhang; Sen Li; Baojiang Sun; Chloe Huang; Kevin Huang; Yuyang Zeng; Chengcheng Liu (Journal of Marine Science and Engineering, 2023)
In this paper, we present a new stress calculation method for flexible structures, particularly, tensile armors, and apply it to flexible riser fatigue analysis. The method is based on a 3-dimensional curved bar theory. First, the tensile armor center line was described as a cylindrical helix curve; its bent curve length and bending migration length were derived and studied under different friction scenarios. Second, the tensile and bending stiffness was derived with consideration of more accurate shape parameters and the frictional hysteretic effect, and verified through FEA analysis results. Third, we presented the stress calculation formula for tensile armor under tension and bending load. All stress components were considered, including tensile, bending and shear stresses. Fourth, the method was benchmarked with published experimental results on a flexible prototype tension and bending tests, and comparisons showed general agreements. Fifth, the method was applied to an in-service 8″ flexible riser for fatigue assessment and lifetime extension evaluation, and showed the flexible riser has sufficient remaining fatigue life, and is suitable to continue its service under the current operating conditions. Last, conclusions were drawn. We concluded that the presented tensile armor stress calculation method and modelling techniques are valid for flexible riser fatigue analysis. This method is time efficient, and can be implemented into other multi-scale models for riser dynamic analysis. It is also applicable to other similar helix structure stress analysis, such as wire ropes, submarine hoses, and subsea umbilicals.

A powerful helper of azoxystrobin degradation—the unique mechanism of UGT72E2 promoting environmental degradation of azoxystrobin - Yu Wang; Jie Wu; Lingling Zhao; Wei Sun; Sen Yan; Sinuo Tian; Qiao Zhao; Wentao Zhu (Environmental Science and Pollution Research, 2023)

A Machine-Learning-Based Method for Ship Propulsion Power Prediction in Ice - Li Zhou; Qianyang Sun; Shifeng Ding; Sen Han; Aimin Wang (Journal of Marine Science and Engineering, 2023)
In recent years, safety issues respecting polar ship navigation in the presence of ice have become a research hotspot. The accurate prediction of propulsion power plays an important role in ensuring safe ship navigation and evaluating ship navigation ability, and deep learning has been widely applied in the field of shipping, of which the artificial neural network (ANN) is a common method. This study combines the scientific problems of ice resistance and propulsion power for polar ship design, focusing on the design of an ANN model for predicting the propulsion power of polar ships. Reference is made to the traditional propulsion power requirements of various classification societies, as well as ship model test and full-scale test data, to select appropriate input features and a training dataset. Three prediction methods are considered: building a radial basis function–particle swarm optimization algorithm (RBF-PSO) model to directly predict the propulsion power; based on the full-scale test and model test data, calculating the propulsion power using the Finnish–Swedish Ice Class Rules (FSICR) formula; using an ice resistance artificial neural network model (ANN-IR) to predict the ice resistance and calculate the propulsion power using the FSICR formula. Prediction errors are determined, and a sensitivity analysis is carried out with respect to the relevant parameters of propulsion power based on the above methods. This study shows that the RBF-PSO model based on nine feature inputs has a reasonable generalization effect. Compared with the data of the ship model test and full-scale test, the average error is about 14%, which shows that the method has high accuracy and can be used as a propulsion power prediction tool.

Emission characteristics of benzene series in FCC flue gas - Bohan Wang; Sen Li; DongXu Sun; Jiawei Bian; Hai Zhao; Hong Li; Yang Zhang; Feng Ju; Hao Ling (Chemosphere, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

A new aeolian activity proxy based on analysis of the grain size characteristics of surface soils across the Tengger Desert, northwest China, and its application to a Quaternary aeolian succession - Bing Liu; Hui Zhao; Fan Yang; Aiming Liang; Aijun Sun; Qinghe Niu; Sen Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

TaMADS29 interacts with TaNF-YB1 to synergistically regulate early grain development in bread wheat - Guoyu Liu; Runqi Zhang; Sen Li; Rehmat Ullah; Fengping Yang; Zihao Wang; Weilong Guo; Mingshan You; Baoyun Li; Chaojie Xie; Liangsheng Wang; Jie Liu; et al. (Science China Life Sciences, 2023)

Chlorothalonil induces obesity in mice by regulating host gut microbiota and bile acids metabolism via FXR pathways - Zhiyuan Meng; Sen Yan; Wei Sun; Jin Yan; Miaomiao Teng; Ming Jia; Sinuo Tian; Zhiqiang Zhou; Wentao Zhu (Journal of Hazardous Materials, 2023)

Construction of lipopeptide mono-producing Bacillus strains and comparison of their antimicrobial activity - Guojun Wu; Jingjie Zhou; Jie Zheng; Dyaaaldin Abdalmegeed; Jingjing Tian; Mengxi Wang; Shengwei Sun; Rita-Cindy Aye-Ayire Sedjoah; Yuting Shao; Sen Sun; Zhihong Xin (Food Bioscience, 2023)

Tomato recognition and location algorithm based on improved YOLOv5 - Tianhua Li; Meng Sun; Qinghai He; Guanshan Zhang; Guoying Shi; Xiaoming Ding; Sen Lin (Computers and Electronics in Agriculture, 2023)

Muyocoxanthones O–S: Undescribed xanthones with antioxidative damage bioactivity to cardiomyocytes from the endophytic fungus Muyocopron laterale - Hai-Yan Cao; Sen-feng Sun; Cheng Yi; Chen-yu Yang; Ke-liang Chen; Xiao-wei Zhang; Yun-Bao Liu (Phytochemistry, 2023)

A new strategy to alleviate the obesity induced by endocrine disruptors—A unique lysine metabolic pathway of nanoselenium Siraitia grosvenorii to repair gut microbiota and resist obesity - Yu Wang; Wei Sun; Sen Yan; Zhiyuan Meng; Ming Jia; Sinuo Tian; Shiran Huang; Xiaoxuan Sun; Shihang Han; Canping Pan; Jinling Diao; Qiuxia Wang; et al. (Food and Chemical Toxicology, 2023)

An injectable and rapidly degraded carboxymethyl chitosan/polyethylene glycol hydrogel for postoperative antiadhesion - Meiyue Wang; Sen Lin; Mengzhe Liu; Jing Jiao; Hongyan Mi; Jingjing Sun; Yiming Liu; Ruiying Guo; Sirui Liu; Haojie Fu; Yanyu Yang; Rui Li (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Nano-sized alumina supported palladium catalysts for methane combustion with excellent thermal stability - Wei Shi; Guangyan Xu; Xuewang Han; Yingjie Wang; Zhi Liu; Sen Xue; Nannan Sun; Xiaoyan Shi; Yunbo Yu; Hong He (Journal of Environmental Sciences, 2023)

Melon yellow-green plant (Cmygp) encodes a Golden2-like transcription factor regulating chlorophyll synthesis and chloroplast development - Sen Yang; Xiaojuan Wang; Wenkai Yan; Yu Zhang; Pengyao Song; Yaomiao Guo; Kuixi Xie; Jianbin Hu; Juan Hou; Yufeng Wu; Huayu Zhu; Shouru Sun; et al. (Theoretical and Applied Genetics, 2023)

Study on properties of sewage sludge cemented paste backfill and leaching mechanism of heavy metals - Sen Chen; Yin Liu; Jiyan Ma; Yujiao Du; Chang Sun (Environmental Science and Pollution Research, 2023)

Synergistic effect of combined sucrose substitutes and partially gelatinized oat flour on gluten-free steamed oat cakes produced only by oat flour - Binghua Sun; Xiaojie Qian; Gengjie Cui; Sen Ma; Xiaoxi Wang (Journal of Cereal Science, 2023)

Effects of gelatinization degree and boiling water kneading on the rheology characteristics of gluten-free oat dough - Yujuan Gu; Xiaojie Qian; Binghua Sun; Xiaoxi Wang; Sen Ma (Food Chemistry, 2023)

Numerical simulation of free-surface waves past semi-submerged two-dimensional rectangular prisms with different aspect ratios and rounding chamfer radii - Sen Qu; Shengnan Liu; Muk Chen Ong; Xikun Wang; Shuzheng Sun (Ocean Engineering, 2023)

The Adsorption and Desorption Behavior of Bisphenol A on Five Microplastics Under Simulated Gastrointestinal Conditions - Hui Jiang; Qiao-ying Li; Jiao-xia Sun; Yu-feng Mao; Xin Liu; Sisi Que; Weiwei Yu; Yi-sen Kan (Water, Air, & Soil Pollution, 2023)

Subculture and Etiolation Treatment Promotes Rooting Ability of Upper Branches of Black Locust Crown - Jie Zhang; Ye Zhao; Anan Duan; Wei Wang; Yuhan Sun; Li Dong; Sen Cao; Xiuyu Li; Xiaodi Liu; Chao Han; Saleem Uddin; Wei Bi; et al. (Forest Science, 2023)
The black locust (Robinia pseudoacacia L.) is an economically and ecologically important tree worldwide. However, maturation and position effects affect its asexual reproduction. Despite etiolation treatment and successive subcultures promoting the plant cutting’s rooting rate, whether the promoting effects of aging (upper) branches and young (lower) branches are consistent is unknown. Therefore, we evaluated the relevant rooting ability indicators of tree age effect and its location effect in 26-year-old R. pseudoacacia trees and the current-year branches of different parts. Branches of the upper and lower parts of these trees underwent accelerated germination to generate shoots as explants. We subjected the tissue culture–generated shoots to an etiolation treatment to investigate how the treatment and subculture time affected the rooting ability of the shoot explants induced by different parts of the black locust branch. Tissue culture shoots subjected to the etiolation treatment exhibited a 2–3 day shorter rooting time. Shoots from the upper crown organs achieved a rejuvenation effect, which manifested as enhanced rooting capacity. Our study results provide a theoretical basis for maintaining the juvenility and consistency of clones. Besides having theoretical and practical value, our study also guides the selection of suitable propagation materials for production.

Study on sex-linked region and sex determination candidate gene using a high-quality genome assembly in yellow drum - Sha Sun; Chaowei Song; Fang Han; Qiwei He; Jieping Liu; Sen Zhang; Wei Han; Kun Ye; Zhaofang Han; Zhiyong Wang; Wanbo Li (Aquaculture, 2023)

Hydrochemical evolution processes of multiple-water quality interfaces (fresh/saline water, saline water/brine) on muddy coast under pumping conditions - Qiming Sun; Maosheng Gao; Zhang Wen; Guohua Hou; Xianzhang Dang; Sen Liu; Guangming Zhao (Science of The Total Environment, 2023)

Concentrations, congener patterns, and correlations of unintentional persistent organic pollutants in cement kilns co-processing hazardous waste - Changzhi Chen; Haoyang Wang; Guorui Liu; Bingcheng Lin; Lili Yang; Rong Jin; Yuxiang Sun; Jianping Guo; Yinming Li; Nan Yang; Aihong Li; Changliang Li; et al. (Science of The Total Environment, 2023)

Spying on the peroxynitrite fluctuation during hearing loss enabled by rationally designed fluorescent carbon dots - Haifang Liu; Jianbo Liu; Sen Zhang; Yun Chen; Juanli Zhang; Yuanqiang Sun; Zhenyu Zheng; Sang Hu; Zhaohui Li; Wenxue Tang (Chemical Engineering Journal, 2023)

Phytochemical and underlying mechanism of Mikania micrantha Kunth on antibiotic resistance genes, and pathogenic microbes during chicken manure composting - Yousif Abdelrahman Yousif Abdellah; Yu-Sen Luo; Shan-Shan Sun; Xi Yang; Hong-Yi Ji; Rui-Long Wang (Bioresource Technology, 2023)

Design and Optimization of Multipoint Sampler for Seafloor Sediment Carried by a Deep-Sea Landing Vehicle - Yan Gao; Yue Zhou; Wei Guo; Yifan Fu; Sen Gao; Zhenzhuo Wei; Hongming Sun; Yu Sun (Journal of Marine Science and Engineering, 2022)
The present study proposes a low-energy consumption multipoint sampler carried by a deep-sea landing vehicle (DSLV) to meet the requirements of time series sampling in local areas and location series sampling in wide areas, and an optimization method of sampling structure based on least-squares support-vector machine (LSSVM) surrogate model and a multi-objective particle swarm optimization (MOPSO) algorithm. First, the overall structure and core components, such as the multipoint sampler’s sampling structure, were designed. The optimization variables were the cone angle, sampling tube inner diameter, and sampling tube inner hole length, which were determined by considering the force with which the sampling structure penetrates the seafloor sediment. Then, the sampling process was simulated by the finite element method-smoothed particle hydrodynamics (FEM-SPH) method, while the accurate LSSVM model of force required for sampling and sampling tube volume was established. Finally, the MOPSO algorithm was used for multi-objective optimization of model parameters of sampling structure. The optimal model of sampling structure that can provide theoretical support for the optimal design of multipoint sampler effectively reduces energy consumption and improves sampling efficiency by force required for sampling 25.89% lower and sampling tube volume 34.81% higher than the original model.

Driving factors of spatial–temporal difference in China’s transportation sector carbon productivity: an empirical analysis based on Geodetector method - Changzheng Zhu; Sen Dong; Yijie Sun; Meng Wang; Peiyan Dong; Lihua Xu (Environmental Science and Pollution Research, 2022)

Responses of rice (Oryza sativa L.) plant growth, grain yield and quality, and soil properties to the microplastic occurrence in paddy soil - Sen Chen; Yanfang Feng; Lanfang Han; Detian Li; Yuanyuan Feng; Paramsothy Jeyakumar; Haijun Sun; Weiming Shi; Hailong Wang (Journal of Soils and Sediments, 2022)

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

Effects of long-term cold storage on maternal and progeny fitness of laboratory-reared Harmonia axyridis adults - Yuan-Xing Sun; Ya-Nan Hao; Jing-Jiang Zhou; Chang-Zhong Liu; Sen-Shan Wang (BioControl, 2022)

Development and characterization of 135 SNP markers in chiton Acanthochitona rubrolineatus - Jirui Zhang; Yunqi Song; Chenghong Wang; Shukui Zhang; Zilin Jiang; Yan Ni; Ying Qu; Donghui Sun; Zhikai Xing; Sen Wu; Jiangyong Qu; Xumin Wang; et al. (Conservation Genetics Resources, 2022)

Development and characterization of 177 SNP markers in the mud shrimp Upogebia major - Chenghong Wang; Yunqi Song; Jirui Zhang; Donghui Sun; Ying Qu; Yan Ni; Zilin Jiang; Shukui Zhang; Zhikai Xing; Sen Wu; Jiangyong Qu; Xumin Wang; et al. (Conservation Genetics Resources, 2022)

A Shuttling Protein Kank1 Plays Important Role in the Sex Determination in Yellow Drum - Sha Sun; Jieping Liu; Sen Zhang; Qiwei He; Wei Han; Kun Ye; Fang Han; Wanbo Li; Zhiyong Wang (Frontiers in Marine Science, 2022)
Sex is one of the most important scientific topics, and the existence of sex dimorphism is a conserved feature in vertebrate taxa. The research on sex-determining genes and sex chromosome evolution is a hot topic in biology. The majority of sex-determining genes expressed in somatic cells, and reciprocal interactions between germ cells and somatic cells, are important for gonadal differentiation. However, the knowledge of how signals are transmitted between somatic cells and germ cells remains unclear. In this study, we confirmed the 36 dph was a sex determination critical stage in yellow drum through transcriptome analysis at the early development stages. We further found that Kank1 participated in the germ cells’ motility process in yellow drum through KEGG pathway analysis together with protein-protein interaction network. With the dual-luciferase reporter assay, we detected that Kank1 increased the transcription of dmrt1_Luc gene in CHO cells and 293T cells. Additionally, we observed that Kank1 was not only expressed in the cytoplasm but also in the nucleus in CHO cells through a fluorescence microscope. These results suggest that Kank1 acts as a shuttling protein as in humans and may play a difunctional role at the early gonad development stage in yellow drum, and it not only participated in the germ cells’ motility but also increased the expression of dmrt1 in yellow drum.

Black-Box Modelling and Prediction of Deep-Sea Landing Vehicles Based on Optimised Support Vector Regression - Hongming Sun; Wei Guo; Yanjun Lan; Zhenzhuo Wei; Sen Gao; Yu Sun; Yifan Fu (Journal of Marine Science and Engineering, 2022)
Due to the nonlinearity of the deep-seafloor and complexity of the hydrodynamic force of novel structure platforms, realising an accurate motion mechanism modelling of a deep-sea landing vehicle (DSLV) is difficult. The support vector regression (SVR) model optimised through particle swarm optimisation (PSO) was used to complete the black-box motion modelling and vehicle prediction. In this study, first, the prototype and system composition of the DSLV were proposed, and subsequently, the high-dimensional nonlinear mapping relationship between the motion state and the driving forces was constructed using the SVR of radial basis function. The high-precision model parameter combination was obtained using PSO, and, subsequently, the black-box modelling and prediction of the vehicle were realised. Finally, the effectiveness of the method was verified through multi-body dynamics simulation and scaled test prototype data. The experimental results confirmed that the proposed PSO–SVR model could establish an accurate motion model of the vehicle, and provided a high-precision motion state prediction. Furthermore, with less calculation, the proposed method can reliably apply the model prediction results to the intelligent behaviour control and planning of the vehicle, accelerate the development progress of the prototype, and minimise the economic cost of the research and development process.

Spatial and temporal variability and risk assessment of regional climate change in northern China: a case study in Shandong Province - Hongli Li; Sen Liu; Meishan Yin; Li’ao Zhu; Enshuai Shen; Baodi Sun; San Wang (Natural Hazards, 2022)

Bacterial community dynamics on bats and the implications for pathogen resistance - Aoqiang Li; Zhongle Li; Wentao Dai; Katy L. Parise; Haixia Leng; Longru Jin; Sen Liu; Keping Sun; Joseph R. Hoyt; Jiang Feng (Environmental Microbiology, 2022)
Summary The bats skin microbiota plays an important role in reducing pathogen infection, including the deadly fungal pathogen Pseudogymnoascus destructans , the causative agent of white‐nose syndrome. However, the dynamic of skin bacterial communities response to environmental perturbations remains poorly described. We characterized skin bacterial community over time and space in Rhinolophus ferrumequinum , a species with high resistance to the infection with P . destructans . We collected environmental covariate data to determine what factors influenced changes in community structure. We observed significant temporal and spatial shifts in the skin bacterial community, which was mainly associated with variation in operational taxonomic units. The skin bacterial community differed by the environmental microbial reservoirs and was most influenced by host body condition, bat roosting temperature and geographic distance between sites, but was not influenced by pathogen infection. Furthermore, the skin microbiota was enriched in particular taxa with antifungal abilities, such as Enterococcus , Burkholderia , Flavobacterium , Pseudomonas , Corynebacterium and Rhodococcus . And specific strains of Pseudomonas , Corynebacterium and Rhodococcus even inhibited P . destructans growth. Our findings provide new insights in characterizing the variation in bacterial communities can inform us about the processes of driving community assembly and predict the host's ability to resist or survive pathogen infection.

The Morphology, Mitogenome, Phylogenetic Position, and Symbiotic Bacteria of a New Species of Sclerolinum (Annelida: Siboglinidae) in the South China Sea - Ting Xu; Yanan Sun; Zhi Wang; Arunima Sen; Pei-Yuan Qian; Jian-Wen Qiu (Frontiers in Marine Science, 2022)
Sclerolinum annulatus n. sp. (Annelida: Siboglinidae) is described based on specimens collected from soft sediment of the Haima cold seep in the South China Sea. Morphologically, S . annulatus n. sp. is distinct in having a tube with transverse rings and a forepart (i.e., anterior region) containing one arched row of elongated plaques on both sides of the dorsal furrow. Genome skimming, assembly, and annotation produced a nearly complete mitogenome of S. annulatus n. sp. with 15,553 bp nucleotides that encodes 13 protein-coding genes, two rRNA, and 22 tRNA. Phylogenetic analyses based on the mitochondrial cytochrome c oxidase I ( cox1 ) gene and a concatenated dataset comprising the mitochondrial cox1 and 16S rRNA genes along with the nuclear 18S rRNA gene both strongly support the placement of S . annulatus n. sp. in the genus Sclerolinum Southward, 1961 . Based on cox1 , S . annulatus n. sp. is most closely related to an undescribed siboglinid from off Kushiro in Japan (“Pogonophora” sp. Kushiro-SK-2003). Transmission electron microscopy, microbial 16S rRNA amplicon sequencing, phylogenetic reconstruction, and stable isotope analyses together indicate that S . annulatus n. sp. hosts a single phylotype of sulfur-oxidizing endosymbionts.

Developing a highly efficient regeneration system for leaves of tissue-cultured tetraploid Robinia pseudoacacia L. - Xiuyu Li; Qi Guo; Chao Han; Juan Li; Li Dong; Sen Cao; Zijie Zhang; Yuhan Sun; Ruohan Wang; Yun Li (In Vitro Cellular & Developmental Biology - Plant, 2022)

The branchless gene Clbl in watermelon encoding a TERMINAL FLOWER 1 protein regulates the number of lateral branches - Junling Dou; Huihui Yang; Dongling Sun; Sen Yang; Shouru Sun; Shengjie Zhao; Xuqiang Lu; Huayu Zhu; Dongming Liu; Changsheng Ma; Wenge Liu; Luming Yang (Theoretical and Applied Genetics, 2022)

Divergent Projection Patterns Revealed by Reconstruction of Individual Neurons in Orbitofrontal Cortex - Junjun Wang; Pei Sun; Xiaohua Lv; Sen Jin; Anan Li; Jianxia Kuang; Ning Li; Yadong Gang; Rui Guo; Shaoqun Zeng; Fuqiang Xu; Yu-Hui Zhang (Neuroscience Bulletin, 2021)

The Effects of Different Fluorescent Indicators in Observing the Changes of the Mitochondrial Membrane Potential during Oxidative Stress-Induced Mitochondrial Injury of Cardiac H9c2 Cells - Yahan Sun; Kunyan Zhou; Mali He; Ying Gao; Danjie Zhang; Yanwen Bai; Yuezhao Lai; Mengying Liu; Xuechao Han; Sen Xu; Wei Tian; Jingman Xu (Journal of Fluorescence, 2020)

Stability assessment of tunnel slopes along the Dujiangyan City to Siguniang Mountain Railway, China - Junpeng Huang; Chunwei Sun; Xiyong Wu; Sixiang Ling; Sen Wang; Rui Deng (Bulletin of Engineering Geology and the Environment, 2020)

Bioaccumulation and toxic effects of penconazole in earthworms (Eisenia fetida) following soil exposure - Ruisheng Li; Zhiyuan Meng; Wei Sun; Ruoyue Wu; Ming Jia; Sen Yan; Sinuo Tian; Wentao Zhu; Zhiqiang Zhou (Environmental Science and Pollution Research, 2020)

A novel plant protein-disulfide isomerase participates in resistance response against the TYLCV in tomato - Tong Li; Ya-Hui Wang; Ying Huang; Jie-Xia Liu; Guo-Ming Xing; Sheng Sun; Sen Li; Zhi-Sheng Xu; Ai-Sheng Xiong (Planta, 2020)

Enhanced Antitumor Efficacy of Curcumin-Loaded PLGA Nanoparticles Coated with Unique Fungal Hydrophobin - Lu Sun; Hui Xu; Jing-hua Xu; Shao-ning Wang; Jun-wei Wang; Hong-feng Zhang; Wei-ru Jia; Lin-sen Li (AAPS PharmSciTech, 2020)

Estimation of precipitation recharge coefficient with a GIS-based method in Zhuanlongwan study area, China - Sen Xue; Peng Xie; Qiyou Zhou; Yun Wu; Mengya Sun; Guyu Zhou; Zhuo Chen (Arabian Journal of Geosciences, 2020)

Induction of Brain Arteriovenous Malformation Through CRISPR/Cas9-Mediated Somatic Alk1 Gene Mutations in Adult Mice - Wan Zhu; Daniel Saw; Miriam Weiss; Zhengda Sun; Meng Wei; Sonali Shaligram; Sen Wang; Hua Su (Translational Stroke Research, 2019)

Pelagiphages in the Podoviridae family integrate into host genomes - Yanlin Zhao; Fang Qin; Rui Zhang; Stephen J. Giovannoni; Zefeng Zhang; Jing Sun; Sen Du; Christopher Rensing (Environmental Microbiology, 2019)
Summary The Pelagibacterales order (SAR11) in Alphaproteobacteria dominates marine surface bacterioplankton communities, where it plays a key role in carbon and nutrient cycling. SAR11 phages, known as pelagiphages, are among the most abundant phages in the ocean. Four pelagiphages that infect Pelagibacter HTCC1062 have been reported. Here, we report 11 new pelagiphages in the Podoviridae family. Comparative genomics classified these pelagiphages into the HTVC019Pvirus genus, which includes the previously reported pelagiphages HTVC011P and HTVC019P. Phylogenomic analysis clustered HTVC019Pvirus pelagiphages into three subgroups. Integrases were identified in all but one HTVC019Pvirus genome. Site‐specific integration of HTVC019Pvirus pelagiphages into host tRNA genes was verified experimentally, demonstrating the capacity of these pelagiphages to propagate by both lytic and lysogenic infection. Evidence of pelagiphage integration was also retrieved from the Global Ocean Survey database, showing that prophages are found in natural SAR11 populations. HTVC019Pvirus pelagiphages could impact SAR11 populations by a variety of mechanisms, including mortality, genetic transduction and prophage‐induced viral immunity. HTVC019Pvirus pelagiphages are a rare example of cultured lysogenic phage that can be implicated in ecological processes on broad scales. These pelagiphages have the potential to become a useful model for investigating strategies of host infection and phage‐dependent horizontal gene transfer.

Lasiodiplodia spp. associated with Aquilaria crassna in Laos - Yu Wang; Sen Lin; Lin Zhao; Xiang Sun; Wei He; Ying Zhang; Yu-Cheng Dai (Mycological Progress, 2019)

Insect microbial symbionts as a novel source for biotechnology - Sen Xie; Yahua Lan; Chao Sun; Yongqi Shao (World Journal of Microbiology and Biotechnology, 2019)

Simulation of the osmosis-based drug encapsulation in erythrocytes - Duobiao Ge; Lili Zou; Chengpan Li; Sen Liu; Shibo Li; Sijie Sun; Weiping Ding (European Biophysics Journal, 2018)

Decadal-scale teleconnection between South Atlantic SST and southeast Australia surface air temperature in austral summer - Jiaqing Xue; Jianping Li; Cheng Sun; Sen Zhao; Jiangyu Mao; Di Dong; Yanjie Li; Juan Feng (Climate Dynamics, 2018)

Association analysis of the SNP (rs345476947) in the FUT2 gene with the production and reproductive traits in pigs - Haifei Wang; Sen Wu; Jiayun Wu; Shouyong Sun; Shenglong Wu; Wenbin Bao (Genes & Genomics, 2018)

Calcification response of Pleurochrysis carterae to iron concentrations in batch incubations: implication for the marine biogeochemical cycle - Xiang Zou; Shiyong Sun; Sen Lin; Kexuan Shen; Faqin Dong; Daoyong Tan; Xiaoqin Nie; Mingxue Liu; Jie Wei (Frontiers of Earth Science, 2017)

Identification of Novel Compound Mutations in PLA2G6-Associated Neurodegeneration Patient with Characteristic MRI Imaging - Sen Guo; Liu Yang; Huijie Liu; Wei Chen; Jinchen Li; Ping Yu; Zhong Sheng Sun; Xiang Chen; Jie Du; Tao Cai (Molecular Neurobiology, 2017)

Utilization of iron sulfides for wastewater treatment: a critical review - Yan Yang; Tianhu Chen; Mukherjee Sumona; Bhaskar Sen Gupta; Yubin Sun; Zhenhu Hu; Xinmin Zhan (Reviews in Environmental Science and Bio/Technology, 2017)

Comprehensive analysis of genomic variation of Hop stunt viroid - Yeonhwa Jo; Hyosub Chu; Hangil Kim; Jin Kyong Cho; Sen Lian; Hoseong Choi; Sang-Min Kim; Sun-Lim Kim; Bong Choon Lee; Won Kyong Cho (European Journal of Plant Pathology, 2017)

Neutrophil-To-Lymphocyte Ratio Predicts 3-Month Outcome of Acute Ischemic Stroke - Sen Qun; Yan Tang; Jing Sun; Zhaoxia Liu; Juncang Wu; Ji Zhang; Jidong Guo; Zhiqiang Xu; Dan Zhang; Zhengxu Chen; Fuyong Hu; Xingshun Xu; et al. (Neurotoxicity Research, 2017)

Comparison of vitrified outcomes between human early blastocysts and expanded blastocysts - Wen-yan Song; Xue-gai Wang; Hai-xia Jin; Gui-dong Yao; Xiang-yang Zhang; Sen-lin Shi; Hong-yi Yang; Zhao-feng Peng; Ying-pu Sun (In Vitro Cellular & Developmental Biology - Animal, 2016)

A case study of an enhanced eutrophication model with stoichiometric zooplankton growth sub-model calibrated by Bayesian method - Likun Yang; Sen Peng; Jingmei Sun; Xinhua Zhao; Xia Li (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Changes in soil organic carbon and total nitrogen in croplands converted to walnut-based agroforestry systems and orchards in southeastern Loess Plateau of China - Sen Lu; Ping Meng; Jinsong Zhang; Changjun Yin; Shiyou Sun (Environmental Monitoring and Assessment, 2015)

Four genetic variants interact to confer susceptibility to atopic dermatitis in Chinese Han population - Changbing Shen; Longdan Liu; Zengqiong Jiang; Xiaodong Zheng; Li Meng; Xianyong Yin; Jing Gao; Yujun Sheng; Jingping Gao; Yang Li; Fusheng Zhou; Fengli Xiao; et al. (Molecular Genetics and Genomics, 2015)

Catechin ameliorates cardiac dysfunction in rats with chronic heart failure by regulating the balance between Th17 and Treg cells - Qi Zhang; Li-qun Hu; Chang-sen Yin; Ping Chen; Hong-qi Li; Xin Sun; Guang Yan (Inflammation Research, 2014)

Association between the TP53 polymorphisms and lung cancer risk: a meta-analysis - Xiang-Hua Ye; Zhi-Bin Bu; Jie Feng; Ling Peng; Xin-Biao Liao; Xin-Li Zhu; Xiao-li Sun; Hao-Gang Yu; Dan-Fang Yan; Sen-Xiang Yan (Molecular Biology Reports, 2014)

The short chain cell-permeable ceramide (C6) restores cell apoptosis and perifosine sensitivity in cultured glioblastoma cells - Li-sen Qin; Zheng-quan Yu; Shi-ming Zhang; Guan Sun; Jian Zhu; Jin Xu; Jun Guo; Lin-shan Fu (Molecular Biology Reports, 2013)

The association between a single nucleotide polymorphism rs11966200 in MHC region and clinical features of generalized vitiligo in Chinese Han population - Jin Tang; Jian Lan Liu; Cheng Zhang; Da Yan Hu; Su Min He; Xian Bo Zuo; Pei Guang Wang; Liang Dan Sun; Xue Jun Zhang; Sen Yang (Molecular Biology Reports, 2013)

The hindgut lumen prokaryotic microbiota of the termite R eticulitermes flavipes and its responses to dietary lignocellulose composition - Drion G. Boucias; Yunpeng Cai; Yijun Sun; Verena‐Ulrike Lietze; Ruchira Sen; Rhitoban Raychoudhury; Michael E. Scharf (Molecular Ecology, 2013)
Reticulitermes flavipes (Isoptera: Rhinotermitidae) is a highly eusocial insect that thrives on recalcitrant lignocellulosic diets through nutritional symbioses with gut‐dwelling prokaryotes and eukaryotes. In the R . flavipes hindgut, there are up to 12 eukaryotic protozoan symbionts; the number of prokaryotic symbionts has been estimated in the hundreds. Despite its biological relevance, this diverse community, to date, has been investigated only by culture‐ and cloning‐dependent methods. Moreover, it is unclear how termite gut microbiomes respond to diet changes and what roles they play in lignocellulose digestion. This study utilized high‐throughput 454 pyrosequencing of 16S V5‐V6 amplicons to sample the hindgut lumen prokaryotic microbiota of R . flavipes and to examine compositional changes in response to lignin‐rich and lignin‐poor cellulose diets after a 7‐day feeding period. Of the ~475 000 high‐quality reads that were obtained, 99.9% were annotated as bacteria and 0.11% as archaea. Major bacterial phyla included Spirochaetes (24.9%), Elusimicrobia (19.8%), Firmicutes (17.8%), Bacteroidetes (14.1%), Proteobacteria (11.4%), Fibrobacteres (5.8%), Verrucomicrobia (2.0%), Actinobacteria (1.4%) and Tenericutes (1.3%). The R . flavipes hindgut lumen prokaryotic microbiota was found to contain over 4761 species‐level phylotypes. However, diet‐dependent shifts were not statistically significant or uniform across colonies, suggesting significant environmental and/or host genetic impacts on colony‐level microbiome composition. These results provide insights into termite gut microbiome diversity and suggest that (i) the prokaryotic gut microbiota is much more complex than previously estimated, and (ii) environment, founding reproductive pair effects and/or host genetics influence microbiome composition.

Natural epigenetic variation in the female great roundleaf bat (Hipposideros armiger) populations - Sen Liu; Keping Sun; Tinglei Jiang; Jennifer P. Ho; Bao Liu; Jiang Feng (Molecular Genetics and Genomics, 2012)

A single-nucleotide polymorphism of the TNFAIP3 gene is associated with systemic lupus erythematosus in Chinese Han population - Li-Qiong Cai; Zai-Xing Wang; Wen-Sheng Lu; Jian-Wen Han; Liang-Dan Sun; Wen-Hui Du; Shu-Mei Zhang; Xian-Bo Zuo; Xue-Jun Zhang; Sen Yang (Molecular Biology Reports, 2010)

Effects of salinity fluctuation frequency on the growth, molting rate and hemolymph 20-hydroxyecdysone concentration in Juvenile Chinese shrimp, Fenneropenaeus chinensis - Sen Ding; Fang Wang; Hao Sun; Shuanglin Dong (Journal of Ocean University of China, 2009)

Changes in estrogen receptor-α variant (ER-α36) expression during mouse ovary development and oocyte meiotic maturation - Bao-Zeng Xu; Sheng-Li Lin; Mo Li; Jia-Qiao Zhu; Sen Li; Ying-Chun Ouyang; Da-Yuan Chen; Qing-Yuan Sun (Histochemistry and Cell Biology, 2009)

Effects of salinity fluctuation frequency on the osmolarity, Na+-K+-ATPase activity and HSP70 expression in juvenile chinese shrimp, Fenneropenaeus chinensis - Sen Ding; Fang Wang; Hao Sun; Biao Guo; Shuanglin Dong (Journal of Ocean University of China, 2009)

Preparation and bioevaluation of 99mTc-HYNIC-annexin B1 as a novel radioligand for apoptosis imaging - Quan-Yong Luo; Fang Wang; Zhi-Yong Zhang; Yi Zhang; Han-Kui Lu; Shu-Han Sun; Rui-Sen Zhu (Apoptosis, 2008)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)